KETERSEDIAAN HAYATI ZAT BESI, KANDUNGAN ZAT PEMICU DAN PENGHAMBAT PENYERAPAN ZAT BESI DALAM MAKANAN IBU HAMIL - M. Saidin; Almasyhuri Almasyhuri; Sukati Saidin (Persagi, 1998)
The iron content, iron bioavailability (in vitro method), enhancers and inhibitors of iron absorption were investigated in three different staple foods of diets in the district of Boyolali, Central Java. The results revealed that the average iron content of the diets based on rice, corn and cassava were 18.8 mg, 17.8 mg and 19.9 mg, respectively or equal to 34.3%, 32.0% and 35.0% of Recommended Dietary Allowances (RDA) for Indonesia. The average vitamin C content of the diets based on rice, corn and cassava were 21.9 mg (31.3% RDA), 21.1 mg (30.1% RDA) and 17.3 mg (24.7% RDA), respectively. The average of protein content of the diets based on rice, corn and cassava were 47.1 g (78.5% RDA), 50.0 g (83.3% RDA) and 31.1 g (51.8% RDA), respectively. The average content of tannic acid and phytic acid as inhibitors of iron absorption in the diets based on rice, corn and cassava were (1154 mg and 261.5 mg); (980 mg and 342.7 mg) and (838 mg and 341.5 mg), respectively. An addition of 100 mg of vitamin C or papaya fruit (250 mg) into the diets, increased iron bioavailability up to 54.2%. Keywords: iron bioavailability, enhancer agent, inhibitor agent, in vitro.